Pengaruh Bimbingan Berpusat Pada Klien Terhadap Kemandirian Pasien Diabetes Mellitus Tipe 2 - Faridatul Istibsaroh; Yunita Amilia; Ahmad Zaini Arif; Tintin Sukartini; Ima Nadatien (Jurnal Keperawatan Muhammadiyah, 2021)
Background: Diabetes Mellitus is a disease characterized by an increase in blood glucose levels which has a risk of long-term or short-term complications. The inability of the community to carry out treatment independently is one of the causes that affect the ability of Diabetes Mellitus sufferers to carry out activities. Objective: This study aims to analyze the effect of client-centered guidance on independence in Diabetes Mellitus patients.Methods:This study used a quasy-experimental design with a pre-post test control group design approach, The sample in this study was 46 respondents divided into 23 interventions group and 23 control groups. The sampling technique is consecutive sampling. The intervention was given by providing client-centered guidance on day 1 with 4 stages, time duration ± 60 minutes, and evaluation for 7 days. Analysis of data using an independent t-test with a significance level of = 0.05.Results: The results of the t-test independent t-test with the value of P = 0.001, it means is an effect of client-centered guidance on the independence of Diabetes Mellitus patients.Conclusion: Providing client-centered guidance can increase independence and it can as part of nursing care interventions in the form of a support education system.